The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1124/dmd.111.041749
|View full text |Cite
|
Sign up to set email alerts
|

Brain Uptake of the Drug of Abuse γ-Hydroxybutyric Acid in Rats

Abstract: ABSTRACT:␥-Hydroxybutyric acid (GHB) is an endogenous compound and a substrate for the ubiquitous monocarboxylate transporter (MCT) family. GHB is also a drug of abuse due to its sedative/hypnotic and euphoric effects, with overdoses resulting in toxicity and death. The goal of this study was to characterize the distribution of GHB into the brain using in vivo microdialysis and in vitro uptake studies and to determine concentration-effect relationships for GHB in a rat animal model. GHB was administered to rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 37 publications
6
39
0
Order By: Relevance
“…Previous reports have demonstrated that the sedative and hypnotic effects of GHB correlate with its brain concentrations (24, 30). Therefore, our results suggest that the respiratory effects of GHB also correlate with its concentration in the brain and needs to be confirmed in future studies by measuring GHB brain ECF concentrations in the presence of AR-C155858.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have demonstrated that the sedative and hypnotic effects of GHB correlate with its brain concentrations (24, 30). Therefore, our results suggest that the respiratory effects of GHB also correlate with its concentration in the brain and needs to be confirmed in future studies by measuring GHB brain ECF concentrations in the presence of AR-C155858.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no approved treatment strategy for GHB overdose. GHB is a substrate for MCT1, a transporter with ubiquitous distribution in the body and responsible for its oral absorption, renal reabsorption and transport across the BBB (8, 9, 11, 24). GHB has also been shown to be a substrate for SMCT1 in rat thyroid follicular cells (16), however, the importance of SMCT1 in the renal reabsorption of GHB is not yet completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…4B). The uptake of GHB into these cell lines was found to be significantly inhibited by CHC [116]. These data suggest the involvement of MCTs in GHB uptake into the brain.…”
Section: Mcts In Drug Dispositionmentioning
confidence: 97%
“…However, the overall partition coefficient of GHB into the brain was not significantly different at the doses studied which suggested that the distribution of GHB into brain was not capacity limited at the doses studied. Although, based on the K m values that were obtained, the distribution of GHB into the brain could be saturated at higher concentrations such as those observed in overdose situations [116]. …”
Section: Mcts In Drug Dispositionmentioning
confidence: 99%
See 1 more Smart Citation